2009
DOI: 10.1164/rccm.200609-1367oc
|View full text |Cite
|
Sign up to set email alerts
|

Myosin, Transgelin, and Myosin Light Chain Kinase

Abstract: Rationale: Airway smooth muscle (SM) of patients with asthma exhibits a greater velocity of shortening (Vmax) than that of normal subjects, and this is thought to contribute to airway hyperresponsiveness. A greater Vmax can result from increased myosin activation. This has been reported in sensitized human airway SM and in models of asthma. A faster Vmax can also result from the expression of specific contractile proteins that promote faster cross-bridge cycling. This possibility has never been addressed in as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 77 publications
1
45
1
Order By: Relevance
“…Isoforms of MYH11, including SMA, SMB, and SM2 were shown to be upregulated at the gene level in asthmatics when compared with non-asthmatics (Léguillette et al 2009) and were negatively correlated with PC 20 values; however, these findings did not agree with the results of previous studies (Ammit et al 2000;Ma et al 2002;Woodruff et al 2004). Ma et al did not detect SMB in their samples, only SMA (Ma et al 2002).…”
Section: Myosin Heavy Chaincontrasting
confidence: 63%
See 3 more Smart Citations
“…Isoforms of MYH11, including SMA, SMB, and SM2 were shown to be upregulated at the gene level in asthmatics when compared with non-asthmatics (Léguillette et al 2009) and were negatively correlated with PC 20 values; however, these findings did not agree with the results of previous studies (Ammit et al 2000;Ma et al 2002;Woodruff et al 2004). Ma et al did not detect SMB in their samples, only SMA (Ma et al 2002).…”
Section: Myosin Heavy Chaincontrasting
confidence: 63%
“…Interestingly, there was a further increase in the levels of smMLCK in severe asthmatics compared with those with milder disease. Leguillette et al showed increased expression of smMLCK mRNA by quantitative PCR in biopsies from mild to moderate asthmatics (Léguillette et al 2009). The expression of smMLCK protein in the ASM was verified by IHC but not quantified.…”
Section: Myosin Light Chain Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…Non-canonical Wnt signaling activated via WNT-5a ligand is involved in adult tissue homeostasis (Logan and Nusse, 2004; Clevers, 2006). ASM remodeling is mainly characterized by increased muscle mass because of cell hyperplasia and hypertrophy, but increased production of specific types of ECM proteins is also an important step in ASM abnormalities in asthma, as the ASM bundle thickens and expresses more ECM and contractile proteins compared with healthy people (Woodruff et al, 2004; Léguillette et al, 2009; James et al, 2012). In the current study, we sought to better understand and to control eosinophil-induced ASM remodeling caused by altered ASM cell proliferation and ECM protein production.…”
Section: Discussionmentioning
confidence: 99%